Effect of Fibrolytic Microbes and Enzymes on Biochemical Blood Parameters in Crossbred Calves - Kapadiya, RI; Shah, SV; Patel, YG; Pandya, PR (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Twenty crossbred (HF x Kankrej) calves were allotted randomly to five groups (each had one male and three female calves) almost with  similar body weight (85.70 ± 6.37 kg) and age (167.55 ± 21.70 days). Experimental calves of the control group were offered hybrid napier  untreated, and the other four groups were offered hybrid napier treated with (i) fungus- Aspergillus spp. (1×107 per g feed), (ii) fibrolytic  bacteria- Escherichia spp. (106 CFU per g feed), (iii) xylanase (50 mL/kg having xylanase 1.2 IU/mL), and (iv) consortium of 1/3rd dose  of fungus + bacteria + enzyme as treatments for 140 days. The blood samples were collected from each calf at a biweekly intervals in  the EDTA vacuttee. Nutrients offered to crossbred calves were sufficient to satisfy the nutrients requirements. Bacteria fed calves had  significantly higher (p
Keywords: Blood biochemical parameters; Crossbred calves; Fibrolytic enzyme; Fibrolytic microbes; Haemoglobin